(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Cicatricial alopecia (CA) is a heterogeneous group of inflammatory disorders causing irreversible destruction of hair follicle stem cells and their replacement by fibrous tissue, affecting approximately 3-7% of patients presenting to dermatology clinics. Pathogenesis involves lymphocyte- or neutrophil-mediated attack on the pilosebaceous unit, driven by JAK/STAT signaling, Th1/Th2/Th17 cytokine imbalance, and microbial dysbiosis. This review evaluates the quantitative clinical efficacy of biological agents, JAK inhibitors, and platelet-rich plasma in stabilizing disease activity and promoting residual follicular survival.